Mumunine - A New Carbazole Alkaloid from Murraya koenigii (Linn.) Spreng - Chakraborty, M. (Journal of Scientific Research, 2020)
The plant Murraya koenigii, commonly known as curry leaf tree is a rich source of carbazole alkaloids. A number of monomeric as well as dimeric carbazoles with C13, C18 and C23 skeleton have been isolated from the plant. In my present work, a new carbazole alkaloid, designated as mumunine, was isolated from the bark of Murraya koenigii (Linn) Spreng, along with a known carbazole alkaloid, viz. mahanimbine. The structure of the new alkaloid 1 was elucidated on the basis of 1D and 2D NMR spectral data analysis. In this paper, the isolation and structure elucidation of the new compound will be discussed in detail.